Unveiling the intersection of technology and pedagogy: a domain-specific exploration for developing religious moderation content with an exploratory and Rasch Perspective - Hanafi, Yusuf; Saefi, Muhammad; Ikhsan, M. Alifudin; Diyana, Tsania Nur; Ahsanuddin, Mohammad; Alfan, Muhammad; Yani, Muhammad Turhan; Hazin, Mufarrihul; Chamidah, Dewi; Mustakim, Siti Salina (Informa UK Limited, 2024)
The primary aim of this study was to investigate the construct validity of a survey focussing on the use of technology and teaching techniques to promote religious moderation, employing exploratory factor analysis (EFA). A total of 116 educators, who teach character development courses, were recruited to participate in the study. The developed instrument is based on the Technology Pedagogical Content Knowledge (TPACK) framework and has been validated through expert and cognitive interviews with religious education lecturers. The study’s results demonstrate that participants were able to discern conceptual distinctions between TPACK domains. Four factors were identified: TPACK, Pedagogical Content Knowledge (PCK), Technological Knowledge (TK), and Pedagogical Knowledge (PK). TPACK encompasses both Technological Pedagogical Knowledge (TPK) and Technological Content Knowledge (TCK), while PCK includes Content Knowledge (CK). Additionally, Rasch statistical analysis was employed to determine that the instrument measures a single latent variable, namely religiously moderated TPACK, with high reliability based on the fit of the scale to the Rasch model. The statistical data from the EFA and Rasch analyses suggest that this survey can serve as a valuable tool for researchers and educators interested in exploring TPACK within the context of religious moderation.